IMPROVING THE EXPRESSIVE LANGUAGE ABILITIES OF CHILDREN OF THIS AGE THROUGH INNOVATIVE METHODS IN CALISTUNG - Suriyani, Suriyani; Dewanti, Lucky; Budianti, Baedah (STKIP PGRI Situbondo, 2023)
Singing is the activity of making voices with dubious poems. The method of singing is a method that is very important for children in stimulating the development of the child's language in acknowledging and expressing language. This research is qualitative research, which is a method of research used in the form of descriptive exposure that attempts to describe all the information, symptoms, events, data obtained to be the focus of research then described. This research aims to find out the application of singing methods in developing language expression skills in children aged 4-5 at PAUD Calistung Tonjong Tajurhalag Bogor, with the number of subjects 1 teacher and object 13 students. The data collection techniques that researchers use are observations, interviews and documentation, while the data analysis techniques that they use are data reduction, data display, and conclusion drawings. The results show that the use of singing methods to develop the expressive language skills of children of group A as follows: 1) Early 4-5 years of children's expressive linguistic skills are improved, because using the method of chanting gives a boost in the enthusiasm of fun learning 2) Teachers are developing using various methods of learning to develop aspects of the child's language such as; singing, talking, asking answers, playing roles, and games. 3) The singing methods used by Paud Calistung were successful in enhancing the development of children's language, especially the expressive language of children with appropriate data during pre-research and observation research.